MOOC in Latic America: Implementation and Lessons Learned - Rizzardini, R.; Gütl, Christian; Chang, Vanessa; Morales, M. (Springer, 2013)
A critical review on MOOCs is provided in this paper. A discussion on the different types of MOOCs and the design of a MOOC learning experience in South America forms the basis of this paper. The MOOC presented utilized cloud-based tools for deployment of the learning activities. Findings on usability, emotional and motivation aspects from 143 participants who had completed the MOOC course are discussed in this paper. Restrictions to pre-selected cloud based tools and communication channels as well as guidance provided to the participants revealed positive learners' attitudes on usability, emotional and motivation aspects.